Book Review - Pillar, Paul; Duffield, Mark; Kux, Ambassador Dennis (Tufts Archival Research Center, 2005)
Volume 26, Issue 1. Winter/Spring. Terrorism and U.S. Foreign Policy . Global Governance and the New Wars: The Merging of Development and Security . The United States and Pakistan 1947-2000: Disenchanted Allies. Book Review